Evaluating the efficacy of purchased antisense oligonucleotides to reduce mouse and human tau in vivo - Vemula, Pranav; Schoch, Kathleen M.; Miller, Timothy M. (Frontiers in Molecular Neuroscience, 2023)
Many preclinical and clinical studies support the use of antisense oligonucleotides (ASOs) as effective therapeutic strategies. However, acquiring ASOs for research purposes may be limited by partnerships with the pharmaceutical companies. Our lab previously developed an effective ASO strategy to lower human tau and reverse pathology in aged tauopathy model mice. Testing the efficacy of purchased tau lowering ASOs would provide support for these reagents as broad research tools. Purchased mouse and human tau lowering ASOs were infused or injected intracerebroventricularly into wildtype and tau transgenic mice. Following treatment, brain tissue evaluated for ASO distribution and levels of tau mRNA, protein, and phosphorylated tau. We show that purchased ASOs enter cell types of the brain and effectively decrease mouse or human tau mRNA and protein levels. Human tau lowering ASO treatment in PS19 mice decreased phosphorylated tau and gliosis relative to saline-treated PS19 mice, consistent with our previous study using a non-commercial tau lowering ASO. The results of this study demonstrate the efficacy of purchased tau targeting ASOs in vivo to support their broad use by researchers.